Soul Gravity - Elgezeery, Gamal, 1973- (Book collections on Project MUSE., 2020)
This book contains dozens of haiku sequences. Each sequence consists of many haiku poems that revolve around the same topic and can be read sequentially and spatially. The poems in each sequence complement one another and shed contrastive and corroborative light on one another. They deal with many spiritual, moral, and realistic problems of contemporary humans and seek to develop the nature of haiku poetry itself.